Tran-Duc-Thao and the language of real life. (November 2018) - D'Alonzo, Jacopo
Abstract: From the 1950s, the Vietnamese philosopher Tran-Duc-Thao (1917–1993) became interested in language origins. To him, the way to investigate the roots of human language was to suggest a semiotics that would be free from the primacy of arbitrary signs. Thao called his own semiotic project the 'semiology of real life'. The main source of that label is a passage of Marx's and Engels' German Ideology dealing with 'the language of real life'. Thao's semiotic model may allow us to better understand some of the assumptions and implications of this little-known Marxian notion. Like Marx and Engels, Thao was deeply convinced of the social origins of linguistic skills and insisted that language arose during cooperative collective goal-oriented activities. Thus, Thao regarded the language of real life as coextensive with the material activity and the material intercourse of humans. He went on to describe the motivated structure, the denotative function, and the context-related nature of what he saw as the most fundamental signs in human languages. To him, such signs also illustrated the first step in the development of human-specific linguistic skills. At the same time, in this way, Thao called explicitly into question Saussure's semiotic model.